2022
DOI: 10.3389/fpsyg.2022.1054356
|View full text |Cite
|
Sign up to set email alerts
|

English learning burnout: Scale validation in the Chinese context

Abstract: While there has been considerable research on learning burnout in educational psychology, it has received little attention in language education. To fill this gap, the present study aims at exploring the construct of English learning burnout (ELB) and examining the levels of this complex construct in a large sample of 1,213 Chinese senior high school students utilizing a 15-item Senior High School English Learning Burnout Scale. A two-dimensional structure of ELB comprising exhaustion and demotivation was extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…After the analysis carried out, the results generally showed that the teaching staff considered the critical and positive role of learner's self-learning skills, self-regulation and interest in the English as a Foreign Language (EFL) context in China, which was also recognized in the previous studies (Peng, 2021;Liu & Zhong, 2022). They commented on 4 aspects: English teaching, learners' self-learning, the English education system and learners' language competence.…”
Section: Discussionmentioning
confidence: 70%
“…After the analysis carried out, the results generally showed that the teaching staff considered the critical and positive role of learner's self-learning skills, self-regulation and interest in the English as a Foreign Language (EFL) context in China, which was also recognized in the previous studies (Peng, 2021;Liu & Zhong, 2022). They commented on 4 aspects: English teaching, learners' self-learning, the English education system and learners' language competence.…”
Section: Discussionmentioning
confidence: 70%
“…Another study done by Liu and Zhong (2022), "Scale Validation of English Learning Burnout (ELB) in the Chinese Context," aimed to define the concept of English learning burnout and analyse its prevalence among 1213 Chinese senior high school students by using a 15-item Senior High School English Learning Burnout Scale. The study concluded that ELB is a negative and complex psychological state that can cause learners to feel disinterested, unmotivated by their confidence and interest and even exhausted regarding English learning.…”
Section: 4mentioning
confidence: 99%